2023
DOI: 10.1002/ajpa.24747
|View full text |Cite
|
Sign up to set email alerts
|

Mapping bone microstructure trace element composition: Sr, Ba, Cu, and Pb in an early modern Danish skeleton

Abstract: Objectives A Geographical Information System (GIS) approach enhances the acquisition, management, and analysis of trace element data from cortical bone. A high‐resolution spatial dimension expands the research potential of Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA‐ICP‐MS) data from cortical bone cross‐sections. The chemical characterization of hundreds of osteons, notably sequences of superimposed osteons, permits more exacting studies of individual life histories than is possible with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…For elements such as Pb, the uneven distribution even extends to different parts of osteons (Pemmer et al, 2013;Simpson et al 2021b). That is precisely what has been found in centuries-old Danish archaeological bones (Milner et al, 2023;Rasmussen et al, 2019Rasmussen et al, , 2020b. For example, in the archaeological samples the distribution of Pb within osteons, when visualized through Laser Ablation Inductively Coupled Plasma Mass Spectrometry, is consistent with its concentration in cement lines, the highly mineralized outer margins of osteons, and the borders of central canals (Skedros et al, 2005;Wittig et al, 2019).…”
Section: Postmortem Alteration Of Archaeological Bonesupporting
confidence: 75%
See 4 more Smart Citations
“…For elements such as Pb, the uneven distribution even extends to different parts of osteons (Pemmer et al, 2013;Simpson et al 2021b). That is precisely what has been found in centuries-old Danish archaeological bones (Milner et al, 2023;Rasmussen et al, 2019Rasmussen et al, , 2020b. For example, in the archaeological samples the distribution of Pb within osteons, when visualized through Laser Ablation Inductively Coupled Plasma Mass Spectrometry, is consistent with its concentration in cement lines, the highly mineralized outer margins of osteons, and the borders of central canals (Skedros et al, 2005;Wittig et al, 2019).…”
Section: Postmortem Alteration Of Archaeological Bonesupporting
confidence: 75%
“…The critical issue, of course, is whether long-buried bones have been so thoroughly altered through exposure to soil and groundwater, and whatever contaminants they might contain, that their value for archaeological purposes is fatally compromised. Recent work focused on a cross-section of an archaeological femur from Denmark showed that concentrations of Pb, Cu, and Sr were both high and variable near the cortical bone's surface (Milner et al, 2023). In the interior, however, the concentrations of these three elements varied from one osteon (Haversian system) to the next, not according to an osteon's distance from the exposed surface of the bone.…”
Section: Postmortem Alteration Of Archaeological Bonementioning
confidence: 99%
See 3 more Smart Citations